Darwin wasps of the genus Seticornuta Morley, 1913 (Ichneumonidae: Metopiinae) in the Neotropical region, with a key to species - Alvarado, Mabel (European Journal of Taxonomy, 2022)
The genus Seticornuta Morley, 1913 currently comprises nine described species; here, nine new species are described: S. anchanchu sp. nov., S. carinata sp. nov., S. cuckoo sp. nov., S. curupira sp. nov., S. flava sp. nov., S. muqui sp. nov., S. nigroflava sp. nov., S. quilmes sp. nov., and S. rufa sp. nov. The genus is redescribed to encompass the features found in Neotropical species and distinctions between the species in the New World and Old World are presented. The genus is recorded for the first time for Argentina, Bolivia, Ecuador, Guatemala and Peru.